can some one please give me, step by step, how to solve this problem. once I see how its done ill understand it for the other I have to do. -3(y-2)-y=5
can some one please give me, step by step, how to solve this problem. once I see how its done ill understand it for the other I have to do. -3(y-2)-y=5
If that's meant to me $\displaystyle -3(y-2)-y=5$ then you just multiply out those brackets to get...
$\displaystyle -3y+6-y=5$
Then collect the $\displaystyle y$ terms to get...
$\displaystyle -4y+6=5$
Take the 6 across to the other side to get...
$\displaystyle -4y=-1$
And finally dividing by $\displaystyle -4$ you get...
$\displaystyle y=\frac{1}{4}$
Have no fear, the calvary is here!
$\displaystyle -3(y-2)-4=5$
First distribute the -3 on the left side
$\displaystyle -3y+6-4=5$
Now, combine terms on the left
$\displaystyle -3y+2=5$
Next, subtract 2 from both sides
$\displaystyle -3y=3$
Finally, divide both sides by -3
$\displaystyle y=-1$
Ta-Da!!